2015
DOI: 10.1007/s00253-015-6521-5
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous saccharification and fermentation of cellulose in ionic liquid for efficient production of α-ketoglutaric acid by Yarrowia lipolytica

Abstract: Ionic liquids (ILs) are benign solvents that are highly effective for biomass pretreatment. However, their applications for scale-up biorefinery are limited due to multiple expensive IL recovery and separation steps that are required. To overcome this limitation, it is very critical to develop a compatible enzymatic and microbial biocatalyst system to carry the simultaneous saccharification and fermentation in IL environments (SSF-IL). While enzymatic biocatalysts have been demonstrated to be compatible with v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 61 publications
(69 reference statements)
0
33
0
Order By: Relevance
“…Plasmid pSL16-CEN1-1-227, containing the CYC1 terminator (T CYC1 ) and leucine selection marker, was kindly provided by M. Matsuoka (Sojo University, Japan) (35). Plasmid pSR001 was created by inserting the Y. lipolytica TEF promoter (P TEF ) (36) in front of T CYC1 of pSL16-CEN1-1-227 as described elsewhere (31). The list of primers used in this study is shown in Table S2.…”
Section: Strains and Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmid pSL16-CEN1-1-227, containing the CYC1 terminator (T CYC1 ) and leucine selection marker, was kindly provided by M. Matsuoka (Sojo University, Japan) (35). Plasmid pSR001 was created by inserting the Y. lipolytica TEF promoter (P TEF ) (36) in front of T CYC1 of pSL16-CEN1-1-227 as described elsewhere (31). The list of primers used in this study is shown in Table S2.…”
Section: Strains and Plasmidsmentioning
confidence: 99%
“…Y. lipolytica not only can be harnessed to produce large amounts of intracellular neutral lipids (Ͼ90% of dry cell weight [DCW]) (23,24), oleochemicals (25), food supplements (e.g., omega-3 eicosapentaenoic acid) (26), high-value organics (e.g., citric, ␣-ketoglutaric, succinic, and pyruvic acids), and proteins (e.g., proteases and lipases) (27) but also is capable of assimilating complex substrates (e.g., organic acids, alcohols, triglycerides, and hydrocarbons) (27) as well as of thriving in a wide pH range (pH 2 to 11) (28) and in the presence of inhibitory acid-pretreated biomass hydrolysates (29) or high (Ͼ12% NaCl) salt concentrations (30) or even high (10% [vol/ vol]) concentrations of ionic liquids (31). While native Y. lipolytica has been known for decades to use only some C 6 sugars such as glucose, mannose, and fructose (32), its capability of assimilating other sugars such as xylose and cellobiose and their mixtures with glucose is poorly understood.…”
mentioning
confidence: 99%
“…Since wildtype Y. lipolytica can grow in at least 10% (v/v) [EMIM][OAc] (7), we hypothesize that it has a novel endogenous metabolism conferring exceptional IL robustness. To test this, we performed ALE to generate Y. lipolytica mutants with enhanced tolerance to high concentrations of the benchmark IL, [EMIM][OAc] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These solvents are inhibitory because they severely disrupt cell membranes and intracellular processes (2123). For applications such as simultaneous saccharification and fermentation of IL-pretreated lignocellulosic biomass, microbes that are active in high IL-containing media are desirable because expensive IL washing and recycling steps prior to fermentation are not needed (7, 24). Unfortunately, most industrially-relevant platform organisms, Escherichia coli and Saccharomyces cerevisiae , are severely inhibited in IL-containing media even at low concentrations, for instance, 1% (v/v) [EMIM][OAc] (25, 26).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation